Light-dependent and circadian transcription dynamics in vivo recorded with a destabilized luciferase reporter in neurospora - Cesbron, François; Brunner, Michael; Diernfellner, Axel (PLOS ONE, 2013)
We show that firefly luciferase is a stable protein when expressed at 25°C in Neurospora, which limits its use as transcription reporter. We created a short-lived luciferase by fusing a PEST signal to its C-terminus (LUC-PEST) and applied the LUC-PEST reporter system to record in vivo transcription dynamics associated with the Neurospora circadian clock and its blue-light photosensory system over the course of several days. We show that the tool is suitable to faithfully monitor rapid, but also subtle changes in transcription in a medium to high throughput format.
Gesehen am 18.03.2021